Evaluation of Online Learning on Financial Management Course during Covid-19 Period - Dicki Hartanto; Sri Yuliani (STAI Hubbulwathan Duri, 2022)
This study was purposed to analyze the evaluation of learning in the Financial Management course at the Economic Education Study Program, Tarbiyah and Teacher Training Faculty, UIN Sultan Syarif Kasim Riau. This was carried out since the Covid-19 outbreak has caused learning in financial management courses that were previously carried out offline with direct face-to-face changes to online learning. The population of this research is semester 5 students in 2021, with a total sample of 56 students. The sampling technique was done randomly. Data analysis was carried out qualitatively using questionnaires and interviews. This study concludes that students' understanding of offline learning of Financial Management courses is better than students' understanding of online learning during the Covid-19 period. From the various uses of online media, it is known that Google Classroom is considered the best compared to the use of G-Meet/Zoom and e-Learning.